CORRELATION BETWEEN CHANGES IN SONOGRAPHIC, HISTOPATHOLOGICAL AND LABORATORY INDICES IN DOGS WITH EXPERIMENTAL POST-RENAL OBSTRUCTION - S. G. Bokhari; J. Hou; M. I. Siddiqui; Y. Wu; Y. Wang; H. S. Jun; M. Bilal; A. Noor; M.Asif (Journal of Animal and Plant Sciences, 2015)
Unilateral post-obstructive azotemia clinically manifests as a progressive disease syndrome producing diverse irreversible derangements in renal dynamics. Renal dysfunction was assessed through experimental left ureteral ligation in dogs for 20 days. Sonographic changes in renal tissue, and hematological, biochemical, histopathological and urinalysis indices were evaluated on Day 0 and 1, 3, 5, 8, 11, 15 and 20 days after surgery. Sonography revealed significant increase in renal length, width and depth (P<0.05) post-surgery. Leukograms indicated inflammatory lymphocytosis and leucocytosis with a left shift. Hemograms depicted severe, regenerative, normocytic, normochromic anemia and a strong negative correlation with sonographic length, width and depth; thrombograms revealed significant thrombocytopenia on Day 11 (P<0.01). Biochemical profiles yielded significant hypoproteinemia, hypoalbuminemia, hypernatremia and hyperchloremic acidosis (P<0.01). Total protein concentrations showed moderate inverse correlation, while sodium and albumin concentrations, respectively, showed strong, highly significant correlations with sonographic length and depth. Decreased urine concentrating ability was evidenced by decreased urine specific gravity (USG< 1.030, P<0.05) on Days 2, 6, 8, 10 and 12, and a highly significant correlation with sonographic length, width and depth.Tissue sections depicted Grade 4 (61-80%) damage, exhibiting tubular atrophy with subsequent thinning of the renal parenchyma, anda strong correlation with sonographic length (P<0.01) and depth (P<0.01). Using the formulae, YHP=−11.93+0.072 XL, and YHP= −11.93+0.267 XD, severity of histopathological changes can be depicted from an increase in sonographic length and depth, respectively. Conclusively, B-mode sonography is a sensitive modality since architectural changessignify and correlate with derangements in GFR and cellular and microscopic changes, manifested systemically.
Keywords: Ultrasonography; hematology; serum biochemistry; urinalysis; histopathology